2012
DOI: 10.1002/ange.201203014
|View full text |Cite
|
Sign up to set email alerts
|

Copper Catalyst Activation Driven by Photoinduced Electron Transfer: A Prototype Photolatent Click Catalyst

Abstract: Bei Raumtemperatur inaktiv in Methanol ist der Kupfer(II)‐tren‐ketoprofenat‐Präkatalysator 1 (siehe Bild). Er wird aber rasch und quantitativ durch Bestrahlung mit Licht zu CuI reduziert und ist dann ein sehr reaktiver Klickkatalysator. Wird Luft in das Reaktionsmedium eingebracht, wird die Katalyse ausgeschaltet, Spülen mit Argon und anschließendes Bestrahlen schaltet sie wieder an.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…The presence of the tetradentate tren ligand in 1 might limit the over‐reduction process, by lowering the reduction potential of the Cu II /Cu I and Cu I /Cu 0 , compared with copper salts. The E 1/2 of the Cu II /Cu I couple for 1 measured in acetonitrile was found at a rather low value of −0.34 V vs. SCE 5. Nonetheless, we observed that prolonged irradiation of 1 leads to Cu I to Cu 0 reduction and the formation of copper NPs.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…The presence of the tetradentate tren ligand in 1 might limit the over‐reduction process, by lowering the reduction potential of the Cu II /Cu I and Cu I /Cu 0 , compared with copper salts. The E 1/2 of the Cu II /Cu I couple for 1 measured in acetonitrile was found at a rather low value of −0.34 V vs. SCE 5. Nonetheless, we observed that prolonged irradiation of 1 leads to Cu I to Cu 0 reduction and the formation of copper NPs.…”
Section: Resultsmentioning
confidence: 52%
“…Interestingly, this shows that the reaction medium is not limited to good H‐donating solvents. Indeed, the photoreduction of 1 in CH 2 Cl 2 in the absence of the reactant is sluggish, as approximately 75 % of 1 is reduced after 3 h irradiation 5. However, as described above for the photoreduction in water, under the reaction conditions, the alkyne may serve as a sacrificial reductant.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Thus,for example,crosslinking reactions (such as network formation), [7] surfacemodification methods (such as self-assembled monolayers [8] or polymeric surfaces), [9] or the generation of self-healing materials [10] have been enabled as ac onsequence of its high substrate tolerance as well as its solvent insensitivity usually under low temperatures.Besides the known large number of homogeneous and heterogeneous Cu I -based catalysts,e specially latent catalytic "click" systems have been designed, for example,those which can be triggered by aspecific stimulus. Thus,asite-specific activation of the "click" reaction by triggers such as light, [11] pressure, [8a, 12] or as imple heterogeneous ball-milling procedure [13] have been achieved. However,ah omogeneous mechanochemical "click" system has not yet been developed to the best of our knowledge ( Figure 1).…”
mentioning
confidence: 99%